O's Little Book of Happiness - The Editors of O, The Oprah Magazine (New York Macmillan, 2015)
A sprightly dose of practical and insightful inspiration, a sprinkling of feel-good science, and a bounty of joyful stories by great writers, O's Little Book of Happiness features some of the best writing to have appeared in O, the Oprah Magazine over its fifteen year history. From an ode to the power of questions by Elizabeth Gilbert, a tribute to the animal who taught her everything by Jane Smiley, practical advice about boosting your bliss from Gretchen Rubin, a call to find playful joy in one's life by Brené Brown, a guide to trading stress for serenity by Shonda Rhimes, a moving glimpse inside the mind of Neil deGrasse Tyson, and much, much more, the editors at O. have combed through the magazine's extensive archives to assemble this poignant and rousing collection. With a small trim-size and timed for Mother's Day, O's Little Book of Happiness makes the perfect gift.
Keywords: Happiness -- Women--Psychology -- Self-realization in women -- Conduct of life